Given that "S" varies inversely as "G", it is an Inverse Variation Relationship. Then, it has this form:
[tex]S=\frac{k}{G}[/tex]Where "k" is the Constant of Variation.
Knowing that:
[tex]S=4[/tex]When:
[tex]G=1.8[/tex]You can substitute values and solve for "k":
[tex]\begin{gathered} 4=\frac{k}{1.8} \\ \\ (4)(1.8)=k \\ \\ k=7.2 \end{gathered}[/tex]Then, the equation that models the situation is:
[tex]S=\frac{7.2}{G}[/tex]Substituting this value of "G" into the equation and evaluating:
[tex]G=6[/tex]You get:
[tex]S=\frac{7.2}{6}=1.2[/tex]Hence, the answer is:
[tex]S=1.2[/tex]